Use of FBG sensors for monitoring cracks of the equestrian statue of Bartolomeo Colleoni in Venice (Fracture and Structural Integrity, 2014)
The Bartolomeo Colleoni monument suffered for years damage from the local climate. The process of restoring the Colleoni equestrian statue, started in 2003, allowed to understand how the bronze statue was originally cast and manufactured and the techniques used in its construction. During this process a relevant crack on the right foreleg was investigated in correspondence of the cast-on joining the right foreleg to the front portion of the horse body. The crack was investigated experimentally by Fiber Bragg Grating (FBG) sensors, avoiding any modelling because of the very complex structure of the statue. An array of FBG sensors connected in series was glued on the crack with the aim of capturing live information about the effect of applying stress on the crack opening. The monitoring system was successfully tested during repositioning of the RIDER on the horse and is available for long term inspection of the crack opening evolution.
Keywords: Health monitoring